Travel to India: Cecília Meireles and Octavio Paz - Romano, Luís Antônio Contatori (Caracol, 2012)
Taking into consideration the inderdisciplinary approach that caracterizes Travel Literature, this text aims to analyze the chronicles Cecília Meireles wrote during her stay in India in comparison to fragments of Octavio Paz works in which he tells his impressions of that Asia country. Connection is establisjed between the concept of Travel Literature presented by Fernando Cristóvão and Octavio paz´s approach to poetic language. Plato´s Reminiscence Theory is also concerned due to its resonance for Cecília Meirele´s texts.